Smallholder tilapia farming in Nigeria: Guidelines for best biosecurity practices - Mohamed Din, Mohamed Shariff; Subasinghe, Rohana (WorldFish, 2024)
This comprehensive tilapia biosecurity manual is an integral component of this initiative. The manual provides crucial guidelines and protocols for ensuring the health and biosecurity of smallholder operations that farm tilapia. . This we hope it will prove instrumental in guiding fish farmers across Nigeria to protect their stocks from diseases. This, in turn, will enhance yields and ensure the long-term success of their aquaculture endeavors.